Optimalisasi Anggaran Kas dalam Meningkatkan Efisiensi Pengelolaan Keuangan - Daffany Viroza; Putri Yasmin; Muhammad Rizal (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Cash budget optimization is a crucial aspect of enhancing financial management efficiency within an organization. This study aims to analyze cash budget optimization strategies to improve efficiency and financial stability. Using a descriptive qualitative approach, the research examines factors influencing cash management, including systematic financial planning, cost control, technology utilization, and human resource competency. The findings indicate that implementing an integrated cash budget optimization strategy can enhance operational efficiency, reduce the risk of financial deficits, and improve organizational liquidity. The use of technology in cash management systems also proves to increase financial transparency and accountability in both the public and private sectors. Therefore, cash budget optimization is a strategic step that must be implemented in financial management to achieve long-term efficiency and financial sustainability.